upaya UPAYA PENINGKATAN KETRAMPILAN ISTIMA’ SISWA MELALUI LOMBA GHYNA ARABY - Istiqomah Istiqomah; Nuril Mufidah (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
Ghyna Arabi is a contest of singing Arabic songa. The purpose of this research is to find out the students' Istima Skills Improvement through the Ghyna Arabi Contest. This research is a descriptive qualitative research with observation, interviews and documentation as the data collection methods. The results of the study shows that there is an increasing of students' istima skills. It can be shown by the achievement of learning objectives of istima skill. غينا عربي تغني الأغاني باللغة العربية. الهدف من هذا البحث هو معرفة لتطور مهارة الإستماع الطلاب من خلال مسابقة غينا عربي. هذا البحث هو بحث وصفي نوعي باستخدام طرق جمع البيانات الملاحظة والمقابلات والتوثيق.نتائج هذا البحث أن هناك تطور في مهارة الإستماع الطلاب، ويتضح ذلك من خلال تحقيق أهداف التعليم مهارة الإستماع.